Migração e mobilização urbana: uma etnografia do Grupo de Refugiados e Imigrantes Sem-Teto de São Paulo - Salles, Rafael Tavares [UNIFESP] (2018)
The objective of this dissertation is to ethnograph the itineraries of migrants and refugees from the Group of Refugees and Homeless Immigrants of São Paulo (GRIST) in their search for health care, starting from the premise of Itinerary as a complex and dynamic phenomenon of multiple assemblages, in a process of singular and collective construction, and not just as the simple transit of the subjects by the different official apparatuses. The interlocutors were followed in their paths in an attempt to elucidate their forms of organization and understanding of the process of illness, as well as the paths traced in the search for care.